Histopathological pattern of testicular lesion - Baidya, R; Sigdel, B; Baidya, NL (Journal of Pathology of Nepal, 2017)
Background: Testicular tumors are rare type of tumors affecting adolescents and young adults. The testicular tumors constitute 4th most common cause of death from neoplasm in a younger male.The present study is undertaken to analyze the pattern and age wise distribution of testicular lesions in our hospital. Materials and methods: This was a prospective study done over a period of 4 years from November 2012 to October 2016, after taking approval of the ethics committee and informed consent from the patients. Histopathological slides were retrieved and reviewed for tumor and its subtype. Results: A total of 60 cases of testicular lesions were encountered in our study. Out of the total 60 cases,15% (9/60) were diagnosed as malignant testicular tumor.Most of these tumors were seen between 3rd and 4th decades.Germ cell tumor was the most common type (77.7%) among which seminomas (44.44%) and mixed germ cell tumors(28.57%) were most frequently encountered.Other tumor diagnosed was Non-Hodgkin lymphoma. Non-neoplastic lesions of the testis are most common in the second decade of life. The youngest patient was at birth and oldest was 71 years of age. Out of all non-neoplastic lesions, vascular lesions like torsion and infarction are the most common findings (54.90%) followed by tuberculous abscess (15.68%). Conclusion: Testicular tumors are uncommon in our population. Histopathological spectrum of our study was comparable with other parts of the world,germ cell tumor accounted for highest percentage of cases in neoplastic lesions and torsion and infarction are the common findings in non-neoplastiic lesions of testis.